Pemanfaatan Aplikasi Akuntansi Digital untuk Meningkatkan Kualitas Laporan Keuangan pada Rumah Produksi Tepung Mocaf Bunda Mirna di Desa Beti Ogan Ilir: Utilization of Digital Accounting Applications to Improve the Quality of Financial Reports at the Mother Mirna Mocaf Flour Production House in Beti Ogan Ilir Village - Ladewi, Yuhanis; Junaidi, Junaidi; Zuraidah, Ida; Lutviyah, Lana; Qintara, Muhammad Rifat (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Community Service in Beti Village is carried out to help the community in improving the economy of the community in the village. The people of Beti Village have a dominant livelihood in trading. However, in the era of globalization and the rise of online trading, many customers have switched to online sales, so offline traders have experienced a decrease in income. Conditions like this make some residents change their profession from trading to producing products using raw materials from agriculture in the village. The limited capital owned by Bunda Mirna's production house makes business development slow. To increase this development, additional capital is needed, for that in this community service, they will be assisted in preparing financial reports by SAK EMKM and using simple applications with Excel so that financial reports can be of high quality and get the best opinion from KAP. Furthermore, this audited financial report is used to apply for a loan to creditors/banks.